RANCANG BANGUN KURSI RODA ELEKTRIK UNTUK KONDISI NAIK TURUN TANJAKAN - Syam, Rafiuddin; Mustari, Mustari (Jurnal MEKANIKAL, 2011)
This study aims to find out/design and electronic wheelchair that can go up and down a slope, as an aid facility for people with disabilities and elderly people. The wheelchair uses a relay motor control program applied in a microcontroller controlling a DC Motor. This study is intended to inprove the writer’s skills in designing electric wheelchairs that can go up and down a slope. In terms of academic purpose, it is expected that this research can provide additional knowledge for students, especially the students of Mechanical Engineering Department, Faculty of Engineering, Hasanuddin University about wheelchair design that can be beneficial in increasing production through automation in the field of science and technology. The electric wheelchair is equipped with a microcontroller that can receive instructions from a mover stick. It also has a visual equipment that can facilitate the wheelchair user. The instruction from the mover stick will be directly sent because it is connected to the microcontroller by using a serial cable. The results reveal that the manual wheelchair stick / drive shaft driven directly by the user sends instructions to the microcontroller in accordance with the desired wheelchair movement.The signal will be forwarded to the driver that will drive the motor. In this system, the mover stick functions as a user interface connected to the control system. The control system consists of several electronic chains that function to control the electric wheelchair equipped with components of interface input/output and a driver as the actuator.